Understanding gender injustice in early marriage: Challenges faced by women - Putri Efendi, Devian Ayu; Wahyuningsih, Sri (Universitas Islam Negeri Ar-Raniry, 2024)
The form of gender inequality between women and men outlines the existence of female gender inequality, one of which is the phenomenon of early marriage. Therefore, the aim of this research is to determine the forms of gender inequality in women who commit early marriage. The research method uses a constructivism paradigm with a qualitative descriptive research type. The participants of this study consist of women who have entered into early marriages, while the focal point of investigation lies in discerning the various manifestations of gender injustice experienced within this demographic. Informants were purposefully selected, utilizing purposive sampling techniques to ensure comprehensive representation and depth in data collection. Data collection techniques use observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions. The data validity checking technique uses source triangulation and member checking. The findings of this research underscore the intricate interplay between gender injustice and entrenched cultural norms within the context of early marriage, illuminating the perpetuation of traditions and cultural practices across generations. Specifically, the study reveals pervasive forms of marginalization, subordination, stereotype reinforcement, instances of violence, and the imposition of double workloads experienced by women who engage in early marriages. Gender injustice in women from early marriage views women as having a lower status compared to men. The latest finding is that education is the single most effective weapon in fighting gender inequality and reducing the rate of early marriage.